Decolonizing diasporas : radical mappings of Afro-Atlantic literature - Figueroa-Vásquez, Yomaira C. (Book collections on Project MUSE., 2020)
"Figueroa-Vásquez analyzes Afro-Latinx and Afro-Hispanic artists from Equatorial Guinea, Puerto Rico, the Dominican Republic, and Cuba, revealing the thematic, conceptual, and liberatory tools these artists offer when read in relation to one another"--